(untitled) - Bianca de Mello Guaraldi; Thaís Jerez Jaime; Rafael de Mello Guaraldi; Daniel Fernandes Melo; Osvania Maris Nogueira; Nilton Rodrigues (Sociedade Brasileira de Dermatologia, 2013)
Progressive symmetrical erythrokeratodermia is a rare autosomal dominant genodermatosis with variable penetrance described by Darier in 1911. It is characterized by erythematous and keratotic plaques, sharply defined and symmetrically distributed along the extremities, buttocks and, more rarely, on the face. We report a case of a 55-year-old patient with lesions on the dorsum of the hands, interphalangeal pads, wrists, groin and back feet. This case demonstrates a rare and late diagnosis, clinical profusion and presence of familiar involvement. Eritroqueratodermia simétrica progressiva é uma genodermatose rara de herança autossômica dominante, com penetrância variável, descrita por Darier em 1911. E caracterizada por placas eritematosas e queratósicas, bem delimitadas, simetricamente distribuídas ao longo das extremidades, nádegas e mais raramente face. Os autores relatam o caso de uma paciente de 55 anos apresentando lesões no dorso das mãos, coxins interfalangeanos, punhos, região inguinal e dorso dos pés. O caso demonstra raridade, diagnóstico tardio, exuberância clínica e acometimento familial.